Identifying how small and medium-sized enterprises generate deep customer insight for radical innovation. - Van Maldegem, Ageeth (Cranfield University, 2020)
It is widely recognized that Radical innovation drives growth in Small and Medium-sized firms (SMEs). However, relatively few SMEs develop highly innovative new products and services. An underlying cause of this could be SMEs’ failure to identify customers’ latent — unarticulated — needs. Such Deep Customer Insight (DCI) is a prerequisite to radical innovation and should emerge during the innovation process. DCI requires firms to acquire and absorb new knowledge from customers, something that is known to be challenging for many SMEs. The relevant theoretical perspectives underlying DCI are found in the Market-Based Learning, Customer Involvement, Innovation Management, Design and Entrepreneurial Marketing literatures. However, the extant knowledge was found to be fragmented and incomplete. For example, it is unclear whether formal learning processes and market research methods are applicable to SMEs and the roles of managers and employees in DCI have not been clarified. In addition, extant research has not delineated a clear relationship between the type of insights generated (either current needs or latent needs) and the processes and resources by which they were created. As a consequence, it is unclear how SMEs, with their limited resources, can generate DCI effectively. Using systematic case research, with multiple sources of data, radical innovation projects at six companies were studied. This investigated: 1) SMEs’ DCI practices; 2) The level of insights generated; 3) Managers’ perceptions of the process. The results show that some SMEs generate high-quality insights, while others do not; demonstrating that a company’s research skills are a key prerequisite for successful customer interactions and tap customer knowledge. This shows that managers need to prioritize ‘skills’ when allocating resources to radical innovation projects and contributes to Entrepreneurial Marketing theory. The study also provides a precise understanding of two new concepts, the quality of insights and customer involvement, opening up interesting avenues for future research on SMEs.
Keywords: latent needs; market research; customer involvement; insight quality; Practice Theory; innovation process